2017
DOI: 10.3389/fmicb.2017.00839
|View full text |Cite
|
Sign up to set email alerts
|

RpoN Promotes Pseudomonas aeruginosa Survival in the Presence of Tobramycin

Abstract: Pseudomonas aeruginosa has developed diverse strategies to respond and adapt to antibiotic stress. Among the factors that modulate survival in the presence of antibiotics, alternative sigma factors play an important role. Here, we demonstrate that the alternative sigma factor RpoN (σ54) promotes survival in the presence of tobramycin. The tobramycin-sensitive phenotype of logarithmic phase ΔrpoN mutant cells is suppressed by the loss of the alternative sigma factor RpoS. Transcriptional analysis indicated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 72 publications
3
27
1
Order By: Relevance
“…We employed a clinical laboratory assay for testing bacterial susceptibility or resistance to antibiotics, and found that RpoN* improved antibiotic susceptibility at least two-fold for five different antibiotics, including imipenem. This agrees with work by others that showed RpoN is involved in P. aeruginosa tolerance of carbapenems, quinolones, and tobramycin (3436). Unfortunately, the commercial assay uses predetermined antibiotic concentrations in a 96-well plate, limiting the scope of the molecular roadblock’s effects.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We employed a clinical laboratory assay for testing bacterial susceptibility or resistance to antibiotics, and found that RpoN* improved antibiotic susceptibility at least two-fold for five different antibiotics, including imipenem. This agrees with work by others that showed RpoN is involved in P. aeruginosa tolerance of carbapenems, quinolones, and tobramycin (3436). Unfortunately, the commercial assay uses predetermined antibiotic concentrations in a 96-well plate, limiting the scope of the molecular roadblock’s effects.…”
Section: Discussionsupporting
confidence: 93%
“…We previously reported that RpoN* alters transcription of several genes involved in multidrug efflux pumps that confer natural resistance (38). Additionally, RpoN is implicated in tolerance to various classes of antibiotics (3436). We evaluated the effects of RpoN* on antibiotic susceptibility using a MicroScan Neg MIC 43 panel.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Flagellar motility governs the translational movement towards favourable environments in response to physical or chemical attractants (Ottamann and Miller, ). Moreover, flagellar‐dependent cell motility is essential for the establishment of a mature biofilm, and is thus involved in the ability to attach to host surfaces and to elicit canker lesions on citrus (Li and Wang, ; Malamud et al ., ; Viducic et al ., ; Yaryura et al ., ). In addition, the filament flagellin has been shown to be a pathogen‐associated molecular pattern, inducing innate immune responses in host plants (Zipfel et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Additionally, the expression of oprE is controlled by RpoN under aerobic conditions (20). RpoN also regulates the susceptibility to tobramycin (21), quinolones, and carbapenems (22,23) in P. aeruginosa.…”
mentioning
confidence: 99%